Characterization and dispersion behavior of titanium dioxide as photocatalytic nanoparticles using metal organic chemical vapour deposition system - Othman, Siti Hajar (2011)
Metal organic chemical vapour deposition (MOCVD) is a favourable technique to synthesize nanoparticles owing to the relative ease and simplicity of the process. In the MOCVD system, the presence of heat decomposes gaseous reactants to form a stable solid product. The motivation of the present work was to study the synthesis,doping, characterization, dispersion, and photocatalytic properties of TiO2 nanoparticles synthesized via MOCVD. Computational fluid dynamics (CFD) simulation was utilized to provide better understanding on the MOCVD synthesis system as well as fluid dynamics inside the reactor. It was found that deposition temperature plays an important role in determining the properties of the synthesized TiO2 nanoparticles such as particle size and crystallinity. Crystallinity was determined to have significant influence on photocatalytic activity compared to particle size. The nanoparticles heat treated at temperatures higher than or equal to the deposition temperature had improved photocatalytic activity. Thus, it was deduced that the choice of heat treatment temperature should be made in view of the deposition temperature. Fe doping was found to promote the phase transition, slightly decrease the particle size, and enhance the absorption of TiO2 nanoparticles in the visible spectrum. However, the photocatalytic activity decreased due to the unfavourable location of Fe ion inside the interior matrix of the TiO2 nanoparticles rather than on the exterior surface. For the dispersion study, rupture followed by erosion was determined to be the main break up mechanisms when ultrasonication was employed. 3 weight% of polyacrylic acid with average molecular weight of 2000 g/mol was determined to produce the best dispersion and most stable suspension. The coatings were confirmed to be photocatalytically active. Finally, the CFD simulation results indicate that increasing deposition temperature and reducing carrier gas flowrate increases the surface deposition rate and the amount of TiO2 nanoparticles produced. Temperature plays remarkable part in determining the rate of surface deposition of TiO2 nanoparticles compared to carrier gas flowrate. Flow recirculations were found to occur in the reactor due to protrusion and large temperature gradient. Good mixing of N2 and O2 gases is important to ensure the deposition uniformity. Good agreement between experimental and simulation results lends support to the reliability of the simulations work. In conclusion, this work opens the window towards improving and optimizing the synthesis process of nanoparticles via MOCVD method as well as offers knowledge on the dispersion and stabilization of nanoparticles towards advancement for industrial applications.